Development of a WiFI based human activity detection and recognition system - Ji, Junwei (Nanyang Technological University, 2021)
In today's era, with the rapid development of information technology, people are increasingly inseparable from WIFI. WIFI seems to have become an indispensable part of our lives. Research on WIFI has also attracted more and more attention from the industry. Among them, WIFI-based human behavior recognition has gradually become a hot spot in the research of the Internet of Things.